Optimum economic ordering and preservation technology expenditure strategy facing non-instantaneous degrading inventory as a consequence of composite impact of advertisement, trade-credit besides inflation. (8th March 2022) - Nautiyal, Chanda Thapliyal
The present paper accommodates an inventory model for advertisement as well as price sensitive demand. The paper deals with the non-instantaneous degrading products as a composite impact appertaining to trade-credit besides inflation. Also preservation technology is infused to mitigate the rate of deterioration. The paper rules out the prevailing supposition of zero reaching inventory. Hence shortages are permitted and backlogged partly. The model's principal motive is to determine the optimal plan of ordering which dwindles the sum of expenditure of retailer per unit time. The solution procedure includes derivation of propositions and theorems to achieve optimal policy. Four numerical examples with graphical depictions and a sensitivity analysis are administered to elucidate the conclusions of the inventory models. Managerial perspectives have also been addressed.